ANALISIS PERBANDINGAN KURIKULUM DI INDONESIA DAN JEPANG: STRUKTUR, IMPLEMENTASI, DAN KEBIJAKAN PEMERINTAH - Syaroni, Subkhan; Pramesti, Santika Lya Diah (UHN IGB Sugriwa Denpasar, 2025)
This study aims to compare the curricula of Indonesia and Japan in three key aspects: structure, implementation, and government policies. Using a literature review method, the study reveals that Indonesia's curriculum emphasizes moral and religious values and project-based learning. In contrast, Japan's curriculum focuses more on practical skills and character development through integrated moral education. The implementation of the curriculum in Indonesia faces challenges such as educational infrastructure disparities, whereas Japan successfully applies a uniform system despite academic pressure issues. Government policies play a vital role in supporting innovation and sustainability in education systems, with Japan demonstrating greater stability compared to Indonesia. This study provides recommendations for developing adaptive and relevant educational policies.